REE DIFFUSION IN FELDSPAR - Cherniak D.J. (My University, 2002)
Diffusion of several rare-earth elements has been characterized in natural plagioclase under dry, 1-atm conditions. Polished or cleaved sections of feldspar were surrounded by source powders in Pt capsules and annealed in air. Sources of diffusant were rare-earth aluminate garnet powders produced by combustion synthesis. Prepared sample capsules were annealed for times ranging from 30 min to a few months, at temperatures from 925 to 1350 °C. The REE distributions in the feldspars were profiled by Rutherford Backscattering Spectrometry (RBS).The following Arrhenius relation is obtained for Nd diffusion in oligoclase (An23), for diffusion normal to (010):D=2.3x10-3exp(-425kJmol-1/RT)m2s-1.Diffusion in normal to (001) appears to be slightly faster than diffusion normal to (010).For anorthite (An93), Nd diffusion normal to (010) corresponds to the Arrhenius relation:D=5.9x10-6exp(-398kJmol-1/RT)m2s-1.Diffusion rates of four rare earths (La, Nd, Dy, Yb) were measured in labradorite (An67). For transport normal to (010), the Arrhenius relations are:DLa=1.1x10-2exp(-464kJmol-1/RT)m2s-1DNd=2.4x10-2exp(-477kJm ol-1/RT)m2s-1DDy=7.1x10-3exp(-461kJmol-1/RT)m2s-1DYb=3.2x10 -1exp(-502kJmol-1/RT)m2s-1.Diffusivities for all of the rare earths investigated in labradorite are similar, in contrast to the significant variations in diffusivities among the rare earths noted in zircon and diopside. This observation is consistent with elastic models for diffusion, in which differences in ionic radii among the rare earths will have greater influence on diffusion rates in stiffer lattices such as those of zircon and clinopyroxene than in the more flexible feldspar structure.REE diffusion in all of the feldspar compositions is slower than diffusion of divalent and univalent cations, indicating a decrease in diffusion rates with increasing cation charge. Diffusivities of Nd also vary with plagioclase composition, with diffusion faster in more sodic plagioclase. This trend is similar to that noted for Sr, Pb and Ba diffusion in previous studies, and may be due to the fact that the comparatively greater flexibility of more sodic plagioclase permits easier migration of diffusants through the mineral lattice.
Keywords: RARE-EARTH ELEMENTS; DIFFUSION; PLAGIOCLASE FELDSPARS; RUTHERFORD BACKSCATTERING